Perancangan Kemasan Borondong Andreprok 202 Bagi Dewasa Muda Di Luar Jawa Barat - Ni Wayan Valentina Gayatri Dewi; Olivine Alifaprilina Supriadi (KalaTanda, 2024)
Indonesia is a country rich in diversity, one of which is the diversity of traditional foods. However, traditional food has beenshifted by more attractive contemporary food so that the younger generation is less interested in eating traditional food,one of which is the packaging factor. The people of West Java, especially the Sundanese, have a variety of traditionalfoods, one of which is borondong. There are quite a number of borondong MSMEs in Ibun Subdistrict, most of which areless aware of the importance of visual identity, as well as inappropriate selection for packaging. These are the problemsfaced by Andeprok 202. Therefore, this research aims to design packaging with a distinctive visual identity and choosethe right packaging for Andeprok 202 products. The methods used in data collection are observation, interviews, literature,questionnaires, which are analyzed by visual analysis, comparison matrix, and SWOT analysis. This design is expected tobe a solution to the problems faced by Andeprok 202, so that the packaging can be characterized and can maintain productdurability, which can help borondong compete as a traditional food in the midst of the rise of contemporary food